Evaluating Technopark Service Quality Using The Carter Model And Importance-Performance Analysis (IPA) - Telma Anis Safitri; Katon Muhammad; Zakiyyan Zain Alkaf (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2026)
Technoparks play a pivotal role in fostering regional innovation; however, many in Indonesia face significant challenges, including underutilized facilities and inconsistent service quality, which constrain their overall effectiveness. This study aims to evaluate and enhance the service quality of Technoparks in Java—specifically in Solo, Bandung, and Pekalongan—by implementing the CARTER model, which assesses six dimensions: Compliance, Assurance, Reliability, Tangibles, Empathy, and Responsiveness. A quantitative approach was employed, integrating the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA), further enriched by spatial mapping. The findings reveal varying levels of visitor satisfaction across the locations. Pekalongan Technopark achieved the highest CSI score of 87.41% ("Excellent"), followed by Bandung Technopark at 83.77% ("Good") and Solo Technopark at 82.05% ("Good"). The IPA results highlight that the Empathy and Responsiveness dimensions require significant improvement, particularly at Solo Technopark. Consequently, this study recommends strategic interventions focused on service development tailored to visitor needs, the optimization of underutilized facilities, and the enhancement of human resource quality. These findings serve as a strategic reference for Technopark management to bolster competitiveness and contribute to the sustainable development of local innovation and economic ecosystems.